2019
DOI: 10.1111/cpr.12678
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA MYOSLID functions as a competing endogenous RNA to regulate MCL‐1 expression by sponging miR‐29c‐3p in gastric cancer

Abstract: Objective Long non‐coding RNA (lncRNA) has become an important regulator of many human malignancies. However, the biological role and clinical significance of most lncRNA in gastric cancer (GC) remain unclear. Methods We investigate the biological function, mechanism of action and clinical expression of lncRNA MYOSLID in GC. First, we analysed the differential expression of lncRNA MYOSLID in GC tissues and non‐cancerous tissues by analysing the sequencing data obtained from The Cancer Genome Atlas. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…MYOSLID acts as a ceRNA of miR-29c-3p, causing de-repression of anti-apoptotic gene MCL-1. 62 MYOSLID was also defined as potential biomarker in head and neck squamous cell carcinoma, where it promotes invasion and metastasis by modulating the epithelialmesenchymal transition. 63 SOX21-AS1 has been linked to tumor progression and defined as a prognostic marker in cervical cancer, nephroblastoma, hepatocellular carcinoma, and lung and oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MYOSLID acts as a ceRNA of miR-29c-3p, causing de-repression of anti-apoptotic gene MCL-1. 62 MYOSLID was also defined as potential biomarker in head and neck squamous cell carcinoma, where it promotes invasion and metastasis by modulating the epithelialmesenchymal transition. 63 SOX21-AS1 has been linked to tumor progression and defined as a prognostic marker in cervical cancer, nephroblastoma, hepatocellular carcinoma, and lung and oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We established a protein-protein interaction (PPI) network consisting of 165 nodes and 170 edges and identified 18 hub genes by MCODE plugin in Cytoscape. The 18 hub genes have been reported to be associated with gastric cancer, which are CCND2 [27] STAT3 [28], TP53 [29], MCL1 [30], MYC [31], FOXO1 [32], FOXO3 [33], BCL2L11 [34], GSK3B [35], CDKN1A [36], CDH1 [37], PTEN [38], MTOR [39], MAPK1 [40], CASP3, CDC42[41], SMAD4 [42] and IL6 [43]. All of them were predicted target genes for hsa-miR-197-3p, hsa-miR-451a, hsa-miR-136-5p, hsa-miR-337-3p, hsa-miR-654-3p, hsa-miR-182-5p, hsa-miR-1228-3p, hsa-miR-942-5p, hsa-miR-488-3p and hsa-miR-876-3p, and all these 10 miRNAs were predicted miRNAs for hsa_circ_0001013.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive endogenous RNA (ceRNA) regulatory networks are significant mechanisms by which lncRNAs may exert huge influences on cancer. In the ceRNA networks, 15‐17 lncRNAs act as endogenous molecular sponges that competitively bind to miRNAs, 18 which indirectly regulate the expression level of messenger RNA (mRNA). Numerous experiments have demonstrated that this miRNA‐regulated lncRNA and mRNA network is involved in the development, progression, and invasion of cancer 19 .…”
Section: Introductionmentioning
confidence: 99%